2019
DOI: 10.3390/s19122829
|View full text |Cite
|
Sign up to set email alerts
|

A Dark Target Detection Method Based on the Adjacency Effect: A Case Study on Crack Detection

Abstract: Dark target detection is important for engineering applications but the existing methods do not consider the imaging environment of dark targets, such as the adjacency effect. The adjacency effect will affect the quantitative applications of remote sensing, especially for high contrast images and images with ever-increasing resolution. Further, most studies have focused on how to eliminate the adjacency effect and there is almost no research about the application of the adjacency effect. However, the adjacency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The cracks need to be of sufficient width to appear as dark lines, which is theoretically the width of a pixel. Edge detection methods [25,26,27,28] or machine learning methods [29,30,31,32] are typically employed to identify the locations or widths of cracks. A review of crack detection methods can be found in [33].…”
Section: Image Measurement Of Cracks On Concrete Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cracks need to be of sufficient width to appear as dark lines, which is theoretically the width of a pixel. Edge detection methods [25,26,27,28] or machine learning methods [29,30,31,32] are typically employed to identify the locations or widths of cracks. A review of crack detection methods can be found in [33].…”
Section: Image Measurement Of Cracks On Concrete Surfacesmentioning
confidence: 99%
“…At each level, log (1/ ε ) and log ( N ) can be calculated, as shown in Figure 6c. Further details of calculating the fractal dimension can be found in [26]. Note that, typically, the actual meshes in FAC analyses are more refined, and the number of discretization levels is greater (e.g., 4 levels or higher) than as shown in Figure 6.By applying multi-level mesh refinements (i.e., different sizes of ε ), log ( N ) versus log (1/ ε ) can be plotted on a 2D plot.…”
Section: Damage Indices Based On Image Analysis Of Cracksmentioning
confidence: 99%